Experiences of pet loss in the South African context - Lowen, Kathleen Louise (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
In this research the experience of pet loss in relation to the intensity of grief and the repression of that grief due to societal restrictions was studied in a South African sample of 12 pet owners who had experienced the loss of a pet within 24 months prior to the study. A pilot study was conducted in order to refine the semi-structured interview schedule. Participants were asked about their pets, their experience of pet loss in relation to their feelings before and after the loss and whether they felt they could openly grieve around friends and family. The findings indicated that the intensity of grief experienced by the participants was influenced both by the intensity of their Bond with the pet and the repression of their grief due to assumed social sanctions surrounding mourning the loss of a pet. The findings from the study clearly indicate the necessity for pet loss counselling, however it was clear that societal views surrounding pet loss are shifting, thus allowing pet owners to mourn their loss more openly with family and friends. This indicates a decrease in cases of disenfranchised and complicated grief. Furthermore the impact of pet loss necessitates the social legitimation and acknowledgment of the significance of pet loss in contemporary society as these relationships with pets are an increasingly prominent feature both within and as an alternative to familial systems.
Keywords: Pet loss -- Psychological aspects; Pet loss -- South Africa -- Case studies; Pets -- Death; Pet ownders -- Psychology; Human-animal relationships -- Psychological aspects; Grief